Targeting tumour-astrocyte crosstalk for rational identification of novel therapeutic targets for atypical Teratoid/ Rhabdoid tumours - Porter, Harry (2025)
Atypical Teratoid / Rhabdoid Tumours (AT/RTs) are rare and highly aggressive paediatric brain tumours. AT/RTs frequently arise in the cerebellum but also develop in the supratentorial compartment and spine. They are classified as an embryonal brain tumour by the World Health Organisation (WHO). The majority of AT/RT arise in children under three years of age who experience severe side effects resulting from conventional anti-cancer therapies. Therefore, new non-cytotoxic biologically targeted treatments are urgently required to treat patients with AT/RT to minimise acute and long-term side effects including neurocognitive damage.